Conceptual understanding of 8th grade students based on big ideas: The case of measurement - Kalaycı Eyeoğlu, Özlem; Gökkurt Özdemir, Burçin; Eyeoğlu, Ulvi; Özdemir, Burçin Gökkurt (Duzce University, Faculty of Education, 2021)
This study aims to examine the conceptual understanding of middle-school 8th graders on measurement based on big ideas. To this aim, a case study was carried out with six students from a state middle school. The data were collected through semi-structured interviews with the instrument developed by the researchers and consisting of seven open-ended questions. Both descriptive and content analysis were performed to analyze the data. Descriptive analyses were conducted considering the framework of two big ideas in the area of measurement identified by the NCTM (2000). Content analysis using NVivo was employed in analysing the audio-recorded interviews and written responses. The results revealed students had a limited understanding of measurement. It was also determined that the majority of the students made dimensional estimations, showed a rote-based approach in calculating the perimeter, area and volume, and had difficulties in making sense of these concepts. In addition, the understanding of students regarding the volume was found to be limited to interior volume. Finally, some recommendations were made to develop understanding of measurement of students. © 2023 Elsevier B.V., All rights reserved.
Keywords: Big Idea; Geometry Teaching; Learning Area of Measurement; Middle School Students